2020
DOI: 10.4028/www.scientific.net/msf.992.403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiation Sterilization on the Stress-Strain Properties of Non-Woven Materials -Based on Polypropylene

Abstract: Non-woven materials are widely used for the manufacture of disposable medical clothing and underwear. Radiation is widely used to sterilize single-use medical devices. The paper analyzes the effect of ionizing radiation at absorbed doses of 0-60 kGy on the stress-strain properties of medical non-woven spanmelt material based on polypropylene obtained by blow-molding technology. It has been established that ionizing radiation significantly reduces the breaking load and elongation in the machine and cross direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…17 Thus, summarising the results of the data obtained, according to a comparative assessment of the effects of the existing and proposed methods of WHT of sewing parts, it can be stated that when processing textile material with the existing WHT method, the indicators of fabric thickness, breaking load, and breathability decrease on average by 32.9%, 21.41%, and 22.51%, respectively. Considering the importance of such properties of textile materials as fabric thickness, breaking load, and breathability for ensuring the quality of manufacturing of clothing parts, it can be concluded that the use of a vacuum installation allows maintaining the specified properties of the materials used [17].…”
Section: Resultsmentioning
confidence: 99%
“…17 Thus, summarising the results of the data obtained, according to a comparative assessment of the effects of the existing and proposed methods of WHT of sewing parts, it can be stated that when processing textile material with the existing WHT method, the indicators of fabric thickness, breaking load, and breathability decrease on average by 32.9%, 21.41%, and 22.51%, respectively. Considering the importance of such properties of textile materials as fabric thickness, breaking load, and breathability for ensuring the quality of manufacturing of clothing parts, it can be concluded that the use of a vacuum installation allows maintaining the specified properties of the materials used [17].…”
Section: Resultsmentioning
confidence: 99%
“…The masks were processed as a whole (three layers) and each layer separately. Air permeability was evaluated according to GOST ISO 9237-2013 on an A0003-PC instrument (IDM Instruments, Australia) at a pressure drop of 100 Pa, sample area 20 cm 2 . The water vapor penetration rate (vapor permeability) was determined on a UTX-3100 device (Textest AG, Switzerland) (test area 0.3 cm 2 , t = 25.50 °C).…”
Section: Research Objects and Methodsmentioning
confidence: 99%
“…Nonwoven materials are raw materials for the production of disposable medical products: clothes, underwear, masks [1,2]. In the context of the coronavirus pandemic and the impossibility of quickly producing a large number of medical masks, the task of developing sterilization technologies for medical masks and respirators is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…An example is food waste containers, which are more convenient to throw away with their contents. Or, for example, disposable nonwoven products for hygiene (diapers, feminine hygiene products, napkins for various purposes) are also difficult to recycle and, as a rule, are only disposed of [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%